Innovation capacity of Brazilian wineries: an integrated approach using the fuzzy Delphi and random forest methods - Luis Felipe Dias Lopes; Deoclécio Junior Cardoso da Silva; Clarissa Stefani Teixeira (Wine Economics and Policy)
The innovation capacity of organizations, particularly in the competitive Brazilian wine industry, plays a pivotal role in their performance and competitiveness. This study aimed to identify and validate metrics for assessing the innovation capacity of Brazilian wineries through a two-stage research process. Initially, a systematic literature review was conducted using Scopus and Web of Science databases. This phase was followed by a quantitative analysis involving 44 Brazilian winery managers, utilizing the Fuzzy Delphi and random forest methods to validate and prioritize the dimensions and indicators of innovation capacity. Out of 88 potential indicators spanning eight dimensions, 50 were confirmed as validated through the Fuzzy Delphi method, as their defuzzified values exceeded the predetermined cutoff threshold. Research and development, product and service innovation, and sustainability and environmental initiatives emerged as the most critical dimensions, collectively representing over half of the innovation capacity in the wineries. Additional significant, albeit less dominant, dimensions included customer feedback and relationships, emphasizing the importance of consumer engagement, and process efficiency, highlighting the significance of operational effectiveness. While not as prominently, employee engagement and training, strategic collaboration, and market adaptation and diversification were identified as essential for sustained innovation. This research provides strategic metrics to enhance the competitiveness and sustainability of Brazilian wineries.